Strategi Penggunaan Video Pembelajaran Dalam Konteks Katekese Digital - Fransiska Masandai Jawan; Emmeria Tarihoran (Lumen: Jurnal Pendidikan Agama Katekese dan Pastoral, 2024)
The digital age offers new possibilities for catechesis including the use of video as an effective learning tool. In the context of digital catechesis, strategies for the use of learning videos are becoming increasingly important that can provide religious and moral messages conveyed in ways that are interesting, creative, relevant, and accessible to the wider community. As for the challenges in making and using learning videos, the right strategy is needed. The aim is to provide understanding and expand the range of catechesis. The method used in this writing is a literature study by collecting data obtained from books and journals related to the problem being studied by the author. Digital catechesis is a powerful tool for making religious teachings and moral values available to the wider public and easily accessible anytime and anywhere. Therefore, the author expects strategies for using learning videos in the context of digital catechesis need to be developed to maximize their benefits for many people.